The Influence of Islamic Marketing Mix on Shopee Costumer Loyalty towards Customer Satisfaction: Evidence from Milenial Muslim Jember - Mohamad Mondir; Ahmadiono Ahmadiono; Hari Sukarno (Syntax Corporation Indonesia, 2023)
The improvement of internet creates many e-commerce in Indonesia. E-commerce became a receptacle for millennial generation who want to buy goods and services online. In Indonesia, Shopee is e-commerce that has become market leader. Shopee is using Islamic marketing mix to maintain its position in Indonesian market. The purpose from this research is to analyze the influence of Islamic marketing mix (product, price, place, promotion, process, people and physical evidence) on customer loyalty towards customer satisfaction. This research is quantitative research. The sampling technique used is random sampling and convenience sampling. Skala Likert will be used for measuring the data collected. There are 159 samples from millennial Muslim in Jember for this research. The data that has been collected will be analyzed using path analysis. The result indicated that product, place, promotion and people have significant effect on customer satisfaction while price, process and physical evidence are not significant. Product, promotion and physical evidence also have significant effect on customer loyalty while price, place, process and people are not. Customer satisfaction also has no significant effect on customer loyalty. The result also shows that costumer cannot mediate product, price, place, promotion, process, people and physical evidence towards costumer loyalty.